Climate in Sundaland and Asian monsoon variability during the last deglaciation. (20th June 2018) - Chabangborn, Akkaneewut; Yamoah, Kweku K.A.; Phantuwongraj, Sumet; Choowong, Montri
Abstract: The lack of semi-quantitative paleo data from mainland Southeast Asia, especially from the emergent Sundaland, creates a marked difficulty in following the past Asian monsoon variability. The published pollen records from the adjacent sites to the Sundaland were selected in this study and evaluated for the relationship between taxa and plant functional types (PFTs), and subsequently between PFTs and biome, to eventually reconstruct the semi-quantitative temporal temperature and precipitation profile. In order to comprehend the Asian monsoon modification between 18.5 and 11 ka BP, the derived pollen based temperature and precipitation records were further analyzed together with other selected speleothem records from the Asian monsoon region, with reference to the Greenland and Antarctic ice cores. The warmer temperature in the Southern Hemisphere caused a southward shift of the mean position of the Intertropical Convergent Zone (ITCZ) and weakened the summer monsoon in the Asian monsoon region between 18.5 and 15 ka BP. The Northern Hemisphere temperature played an important role in the Asian monsoon modification between 15 and 13.5 ka BP, where the warmer Northern Hemisphere conditions strengthened the summer monsoon intensity in the Asian monsoon region and moved the mean position of the ITCZ to the north. However, the opposing precipitation pattern between the East and the West Indian Ocean suggested the potential influence of the Walker circulation on the Sundaland climate from 13.5 to 11 ka BP.